Structural modelling and in silico analysis of a thiol-activated cytolysin produced by Bacillus thuringiensis - Auhim , Husam Sabah; Odaa, Nisreen Hadi; Ismail Taban (Iraqi Journal of Science, 2026)
Bacillus thuringiensis (Bt) is a soil-dwelling, Gram-positive bacterium that produces proteins with specific toxic effects against invertebrate organisms. These toxins specifically target insects. This study examined a hypothetical Bt protein for its potential toxicity to mammals. The hypothetical protein was analyzed using various bioinformatics tools, including NCBI BLAST and conserved domain tools. The physicochemical properties were assessed using ExPasy ProtParam, and homology models were generated through automated services. The analysis revealed that the hypothetical protein is a thiol-activated cytolysin, a pore-forming toxin that targets mammalian cells with a signature motif. The toxin has a molecular weight of 52.6 kDa, and its instability index is 25.73, indicating it is stable under physiological conditions. Furthermore, the toxin is expected to exhibit thermal stability, as evidenced by its aliphatic index of 79.52. Three homology modeling services were used, homology modeling identified anthrolysin O, a thiol-activated cytolysin with 97.53% sequence identity, as the closest template. The Swiss model demonstrated superior validation compared to others. The protein folds into four functional domains characteristic of thiol-activated cytolysins: domain 3 likely forms beta-barrel channels, domains 1 and 2 are involved in oligomerization, and domain 4 recognizes cholesterol. Docking analysis revealed hydrophobic binding interactions with 8 of 11 residues in the cholesterol signature motif, including a hydrogen bond with Gly474 (2.29 Å). In conclusion, Bt produces a thermostable cholesterol-dependent cytolysin that shows strong similarity to anthrolysin O and perfringolysin O.